2018
DOI: 10.1165/rcmb.2017-0236oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Macrophage Complement Receptor CRIg by TRIM72 Polarizes Innate Immunity of the Lung

Abstract: The complement system plays a critical role in immune responses against pathogens. However, its identity and regulation in the lung are not fully understood. This study aimed to explore the role of tripartite motif protein (TRIM) 72 in regulating complement receptor (CR) of the Ig superfamily (CRIg) in alveolar macrophage (AM) and innate immunity of the lung. Imaging, absorbance quantification, and flow cytometry were used to evaluate in vitro and in vivo AM phagocytosis with normal, or altered, TRIM72 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…To date, in vitro and in vivo studies have consistently implicated VSIG4 as a receptor of complement C3 on the surface of macrophages playing a vital role in phagocytosis and the clearance of pathogens in the circulation (Helmy et al, 2006;Vogt et al, 2006). Most studies have focused on the function of VSIG4 in phagocytosis (Gorgani et al, 2011;Broadley et al, 2016;Zeng et al, 2016;Nagre et al, 2018), although several recent studies have found that VSIG4 is associated with tumour progression (Liao et al, 2014;Xu et al, 2015;Byun et al, 2017). Normally, VSIG4 is expressed on resting macrophages and expression is lost upon activation, and VSIG4 hi macrophages plays an anti-inflammatory and immunosuppressive role in vivo (Vogt et al, 2006;Irvine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, in vitro and in vivo studies have consistently implicated VSIG4 as a receptor of complement C3 on the surface of macrophages playing a vital role in phagocytosis and the clearance of pathogens in the circulation (Helmy et al, 2006;Vogt et al, 2006). Most studies have focused on the function of VSIG4 in phagocytosis (Gorgani et al, 2011;Broadley et al, 2016;Zeng et al, 2016;Nagre et al, 2018), although several recent studies have found that VSIG4 is associated with tumour progression (Liao et al, 2014;Xu et al, 2015;Byun et al, 2017). Normally, VSIG4 is expressed on resting macrophages and expression is lost upon activation, and VSIG4 hi macrophages plays an anti-inflammatory and immunosuppressive role in vivo (Vogt et al, 2006;Irvine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…4c-d), suggesting improved membrane repair. Next, we crossed the inducible T72OE [11,44] male with the Sftpc-eGFP knock-in female [31] to establish the sftpc-EGFP/WT and Sftpc-EGFP/T72 OE mice. Flow cytometry sorting of eGFP positive cells was used to isolate primary ATII cells from these mice ( Fig.…”
Section: Trim72 Promotes Membrane Repair Of Atii Cellsmentioning
confidence: 99%
“…( D ) Statistics of flow cytometry MFI and the percentage of FITC + cells in WT and TRIM72 KO AMs; n = 3 for both groups, * p < 0.05. This figure is reprinted with permission of the American Thoracic Society 13 .…”
Section: Figurementioning
confidence: 99%
“…For the latter, AMs can recognize the targets opsonized with immunoglobulin (IgG) through their Fcγ receptors (FcγR) or the pathogens coated with complement fragments, C3b and C3bi, through their complement receptors (CR) 11 . Among complement receptors, the CR of the immunoglobulin superfamily (CRIg) is selectively expressed in tissue macrophages 12 , and a recent finding highlighted the role of the CRIg in AM phagocytosis in the context of P. aeruginosa pneumonia 13 .…”
Section: Introductionmentioning
confidence: 99%